KOMPETENSI GURU DALAM PELAKSANAAN PROGRAM BACA TULIS QUR’AN (BTQ) DI SMPN 34 DEPOK - Wirda (PT. Hasba Edukasi Mandiri, 2025)
This study aims to analyze teachers’ competence in implementing the Qur’an Reading and Writing (BTQ) program at SMP Negeri 34 Depok. Teacher competence plays a crucial role in the success of the learning process, particularly in BTQ activities that are closely related to Islamic Education (PAI). As future generations of Muslims, students must be able to read the Qur’an, as learning to read it is an obligation for every Muslim. The BTQ program at SMPN 34 Depok is a mandatory activity for all students as part of the school’s effort to eradicate Qur’anic illiteracy. This research employed a qualitative descriptive method using data collection techniques such as observation, interviews, and documentation. Data were analyzed through three stages: data reduction, data presentation, and conclusion drawing. The study applies the behavioristic theory, which emphasizes the importance of repetition and habit formation in learning to read the Qur’an. The findings show that teachers’ competence in the BTQ program is highly significant, even though not all teachers have an educational background in Qur’anic studies. Teachers can still conduct effective BTQ learning, as the main goal of the program is for students to recognize Arabic letters and read the Qur’an properly upon graduation. The implementation involves grouping students based on gender and reading ability. The main obstacles include limited teaching time and an imbalance between the number of teachers and students. However, the program is strongly supported by the school principal, social services, parents, and the enthusiastic participation of both teachers and students.